Correlations between imatinib plasma trough concentration and adverse reactions in Chinese patients with gastrointestinal stromal tumors. (15th April 2020) - Xia, Yanzhe; Chen, Sile; Luo, Meijuan; Wu, Jingjing; Cai, Shirong; He, Yulong; Chen, Xiao; Zhang, Xinhua
Abstract : Background: Imatinib is the standard treatment for patients with gastrointestinal stromal tumors (GISTs), but there is significant variation in imatinib plasma trough concentrations (Cmin ) among patients. The imatinib Cmin distribution at different doses and the correlation of adverse reactions with Cmin in Chinese patients with GIST from a high‐volume center were evaluated. Methods: From July 1, 2017 to December 31, 2018, patients who were receiving imatinib treatment for GIST were prospectively enrolled. Steady‐state blood samples were obtained from patients who had received same‐dose imatinib treatment for ≥1 month with good compliance. Adverse reactions were recorded during regular follow‐up, and blood samples were collected 24 ± 2 hours after dosing. Liquid chromatography‐tandem mass spectrometry was used to measure drug concentrations. Results: In total, 307 patients who received 367 dose levels were investigated. The imatinib Cmin was 1315 ± 716 ng/mL, 2117 ± 597 ng/mL, and 3844 ± 987 ng/mL in patients who were receiving imatinib 400 mg, 600 mg, and 800 mg daily, respectively. The Cmin was significantly correlated with periorbital and limb edema ( P  < .001), anemia ( P  < .001), and rash ( P  = .037). Nausea and vomiting, diarrhea, and conjunctival hemorrhage also were correlated, but not significantly. A much higher Cmin was observed with severe adverse reactions. There was no correlation between the imatinib Cmin and leukopenia, muscle cramps, or hepatobiliary dysfunction. Conclusions: In Chinese patients with GIST, the imatinib Cmin was higher than that reported for Western populations, especially at higher doses. The Cmin was correlated with periorbital and limb edema, anemia, and rash, suggesting that monitoring the imatinib Cmin should be considered when patients develop severe adverse reactions caused by excessive imatinib plasma concentrations. Abstract : In Chinese patients with gastrointestinal stromal tumors, the imatinib plasma trough concentration (Cmin ) is higher than that reported for Western populations, especially at higher doses. The imatinib Cmin is correlated with periorbital and limb edema, anemia, and rash, suggesting that monitoring the imatinib Cmin should be considered when patients develop severe adverse reactions caused by excessive imatinib plasma concentrations.